Second Joint EuroHaptics Conference and Symposium on Haptic Interfaces for Virtual Environment and Teleoperator Systems (WHC'07 2007
DOI: 10.1109/whc.2007.31
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study: Virtual Fixtures and Shared Control for Rehabilitation of Fine Motor Skills

Abstract: The work presented here discusses the experimental results from comparing Virtual Fixtures (VF) and Shared Control (SC) techniques for rehabilitation of fine motor skills. A prior concept called Haptic Attributes was used to design the Shared Control assistance algorithm. Eight trajectories were chosen from the VMI Test book and were used to train a candidate's non dominant hand using recorded samples from their dominant hands. The results were analyzed with respect to errors for time of completion, RMS positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…A third approach, termed shared control in the literature, serves to modify the dynamics of the system by imposing a control effort that elicits the desired behavior of the participant (O'Malley, Gupta, Gen, & Li, 2006;Griffiths & Gillespie, 2004;Emken & Reinkensmeyer). A comparative study of these last two approaches performed by Srimathveeravalli, Gourishankar, and Kesavadas (2007) showed slightly better performance from the shared control approach over the virtual fixture approach.…”
Section: Introductionmentioning
confidence: 99%
“…A third approach, termed shared control in the literature, serves to modify the dynamics of the system by imposing a control effort that elicits the desired behavior of the participant (O'Malley, Gupta, Gen, & Li, 2006;Griffiths & Gillespie, 2004;Emken & Reinkensmeyer). A comparative study of these last two approaches performed by Srimathveeravalli, Gourishankar, and Kesavadas (2007) showed slightly better performance from the shared control approach over the virtual fixture approach.…”
Section: Introductionmentioning
confidence: 99%
“…Kim [10] developed a programmable handwriting teaching system, and Plimmer [11] developed McSig, a multimodal (auditory, tactile, and force feedback) system for teaching the signature writing for blind students. Researchers at the University at Buffalo have developed a series of studies on motor skill transfer [12][13][14]. They developed the concept of haptic attributes (HA) for the assistance technology of virtual fixture (VF) and shared control (SC) [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers at the University at Buffalo have developed a series of studies on motor skill transfer [12][13][14]. They developed the concept of haptic attributes (HA) for the assistance technology of virtual fixture (VF) and shared control (SC) [12]. They showed that a fine motor action can be parameterized using force and position information.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…O 'Malley, Gupta, Gen, and Li (2006) and Srimathveeravalli, Gourishankar, and Kesavadas (2007) experimentally evaluated and compared the guiding virtual fixtures (GVF) and shared control (SC) techniques in terms of performance enhancement and improved training. O'Malley et al found that GVF and SC are both substantially effective in reducing the task completion time.…”
Section: Introductionmentioning
confidence: 99%